Hydrogen, Biomass and bioenergy : integration pathways for renewable energy applications - Lamb, Jacob J.; Pollet, Bruno G. (Hydrogen and Fuel Cells Primers, 2020)
Hydrogen and Bioenergy: Integration Pathways for Renewable Energy Applications focuses on the nexus between hydrogen and carbon compounds as energy carriers, with a particular focus on renewable energy solutions. This book explores opportunities for integrating hydrogen in the bioenergy value chain, such as adding hydrogen to upgrade biofuels and lower CO2 emissions during production. The book also takes the inverse path to examine hydrogen production by chemical and biological routes from various bioresources, including solid waste, wastewater, agricultural products and algae. This broad coverage of technologies and applications presents a unique resource for researchers and practitioners developing integrated hydrogen and bioenergy technologies.